Waste Legislation and its Impact on Marketing Communication of the Circular Economy in Slovakia - Jánoš, Dominik; Rybanský, Rudolf (Political Preferences, 2020)
The article focuses on the characteristics of circular economy, supporters of the concept of circular economy, legislation and marketing communication in the process of circular economy from theoretical perspective. In the practical part of the paper the results of marketing research are presented. Marketing research is divided into 3 phases and focused on whether the respondents from the sample follow the individual communication tools during the process of shopping for clothes. The aim of the paper is to analyze waste legislation by the means of marketing communication tools in the implementation of the cirucular economy in Slovakia.